Penerapan Fuzzy Tahani untuk Pemilihan Perangkat Smartphone Berbasis Website Berdasarkan Kriteria Membeli - Wijaya, Hendra; Virginia, Maria; Hakim, Lukman (Jurnal Teknik Informatika UNIKA Santo Thomas, 2021)
Smartphones are the result of the development of communication and information technology. The various types of smartphones on the market can cause a problem to arise where prospective buyers can feel confused about choosing what type of smartphone that fits their criteria. In this study, the fuzzy model of the Tahani database system was applied so that the data in the form of selection criteria could be used as information to provide recommendations for choosing a smartphone. The results of this study are a list of smartphone recommendations that have been calculated by the system so that users can use these recommendation references in choosing a smartphone.